A rare case report and literature overview: autoimmune polyglandular syndrome type II - Ergenc, Hasan; Arpaci, Dilek Karakaya; Varım, Ceyhun; Tocoglu, Aysel Gurkan; Tamer, Ali (International Journal of Advances in Medicine, 2017)
Autoimmune diseases are a heterogeneous group of diseases with chronic humoral immune response against different tissue formation. Autoimmune polyglandular syndrome (APS) is also characterized by multiple organ autoimmune dysfunction. 43-year-old male patient was admitted with complaints of anorexia, malaise, rapid darkening on skin under the sun. The patient, stating in his medical background that levothyroxine TB with the diagnosis of hypothyroidism was started three years ago, had hypotension and hyperpigmentation. Hyponatremia, hyperkalemia, autoimmune hypothyroidism, primary adrenal insufficiency and atrophic gastritis was detected in examinations, significant improvements were observed in the general condition of the patient on whom glucocorticoids, and then levothyroxine TB replacement treatments were applied, and in blood pressure and laboratory parameters. Therefore, other organ autoimmunity should be sought in patients admitted with any autoimmune disease and be considered in follow-ups. We aimed to review the literature about APS and remind APS by this case.